Efektivitas Penggunaan Website GEKA.id dalam Peningkatan Pengetahuan tentang Pencegahan Seks Bebas Bagi Remaja pada â€œPIK-R Klorofilâ€ di Kabupaten Kampar - Rizki Aditya Putra; Alda Anggini; Muhamad Husni Tamami; Dian Ashfi Furoida; Ninuk Purnaningsih (Jurnal Penyuluhan, 2022)
The GEKA.id website is an educational website for the prevention of free sex for teenagers, in Kampar Regency. Data in 2020 there are 6,797 AIDS cases in Riau Province, 82 of them are in Kampar Regency, where the cause is 2240 cases due to free sex and 2 percent of cases are teenagers aged 15-19 years. On the other hand, technological advances, various information can be obtained easily. Without guidance and education, teenagers can be plunged into misery free sex. The GEKA.id website is part of the GEKA.id Program implemented with partners, namely the School-level Information and Counseling Center (PIK-R). The purpose of this study was to analyze the effectiveness of using the GEKA.id website in increasing knowledge about the preventing free sex for youth. The method used is an evaluative research method, which is a design or procedure in collecting and analyzing data systematically to determine the success and benefits of a program. The results achieved in the GEKA.id Program are the development of a website with various features, and is equipped with a web usage manual and educational programs. The GEKA.id website has been proven to be effective in increasing adolescent knowledge about the prevention of free sex, and is rated very good based on a user satisfaction survey.